Device-based circumcision: advantages, choice of device and surgical technique - S. V. Kotov; I. S. Pavlov; N. D. Korochkin; E. M. Alekberov (Вестник урологии, 2024)
Introduction. Circumcision is one of the most common surgical procedures for men. WHO programs aimed at reducing HIV transmission have led to the development of various circumcision devices designed to standardize surgical techniques, reduce operating time and the number of complications.Objective. To examine available data on the efficacy and safety of different methods of device-based circumcision.Materials & methods. The results of a search in scientific databases such as eLibrary and PubMed were analyzed using the keywords: "circumcision", "circumcision device", and "phimosis". The search was conducted without regard to date or language of publication. After reviewing the literature, 25 articles were selected that best reflect the topic of device-assisted circumcision for further analysis.Results. Device-based circumcision can significantly reduce surgical time, regardless of the type of device used. Device-based circumcision is the safe treatment method; however, it may have a higher incidence of adverse events compared to the standard circumcision technique. The use of self-suturing devices is preferred over ring devices due to fewer complications, better cosmetic results, and greater patient satisfaction. The article is supplemented with a description of the surgical technique of various options for device-based circumcision.Conclusion. Device-based circumcision is effective and safe treatment method on an outpatient basis, which successfully competes with conventional circumcision of the foreskin.